Literatur als Kultursensibilisierung? Zur Arbeit mit literarischen Texten im interkulturellen Fremdsprachenunterricht - Adamczak, Sylwia (Glottodidactica, 1999)
The development of intercultural understanding and the ability of transcultural communication have become one of the key concepts of foreign language teaching. A necessary precondition of such a complex concept is, of course, the comparison of native and foreign reality that is often only displayed in the form of stereotyped behaviour patterns in textbook dialogues. In teaching foreign literature, however, a literary text can be a suitable means for students to become more aware of the foreign culture by observing and analysing it from an intercultural perspective. This article will therefore emphasize the validity of literary texts for preparing students for not only linguistic but also cultural experience. Thus the author will present current conceptions on the role of literature in foreign language teaching, examine specific criteria of the literary text choice for foreign language teaching purposes and provide an overview of current methodological trends for working with such texts.